Optical Properties and a Simple and General Route for the Rapid Syntheses of Reduced Graphene Oxide–Metal Sulfide Nanocomposites. Issue 2 (20th November 2012) - Bai, Song; Shen, Xiaoping; Zhu, Guoxing; Zhou, Hu; Xu, Huan; Fu, Guohua; Ye, Zhefei
Abstract: A simple and general microwave route is developed for the synthesis of reduced graphene oxide (RGO)–metal sulfide (ZnS, CdS, Ag2 S, and Cu2 S) nanocomposites by a one‐pot reaction of metal salts, sulfur powder, and graphene oxide (GO) in ethylene glycol (EG). In the synthesis, the formation of metal sulfide nanoparticles and the reduction of graphene oxide nanosheets happen simultaneously, which results in the in situ formation of metal sulfide nanoparticles on RGO nanosheets with homogeneous distribution. EG acts simultaneously as a solvent, a microwave absorbent, and a reductant. The as‐synthesized products are characterized by powder X‐ray diffraction (XRD), inductively coupled plasma optical emission spectrometry (ICP‐OES), energy dispersive X‐ray spectroscopy (EDS), and transmission electron microscopy (TEM). The influence of synthetic parameters such as the concentration of reactants on the size, morphology, and distribution of metal sulfide nanoparticles on RGO nanosheets is also investigated. The optical properties of the as‐synthesized nanocomposites are studied through UV/Vis and photoluminescence (PL) spectroscopy. It is believed that this simple and versatile method presented here can be extended to prepare other graphene‐based metal chalcogenide nanocomposites with various functions. Abstract : A general microwave route is developed for the synthesis of reduced graphene oxide (RGO)–metal sulfide nanocomposites, and a mechanism for the formation of the nanocomposites is proposed. The RGO–metal sulfide nanocomposites are photoluminescent in the UV/Vis and near IR (NIR) regions. This method could be extended to the synthesis of other RGO–metal chalcogenide nanocomposites.